A MATHEMATICAL APPROACH FOR EVALUATION OF THE PURCHASED QUANTITIES OF SEVERAL TYPES OF MEAT AVERAGE PER HOUSEHOLD - Delyana DIMOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The current paper presents a mathematical approach for evaluation of the purchased quantities of several types of meat average per household in Bulgaria. The investigated groups of data are stored in a relational database. They include the following eight considered elements - pork meat, lamb meat, minced meat, poultry meat, mutton and goat meat, edible offals and bacon. Certain set of variables have been calculated and analysed during the studied period (2010-2021). The pace of change of the indicated variableshas also been discussed for the mentioned years. It significantly supports users in decision making and presenting the obtained conclusions about the examined objects.The share of average purchased quantities per household for poultry meat is higher in comparison with that for the other investigated types of meat for each one year of the period. The pace of change of the examined indicator for the pork meat is comparatively more intensive in 2019-2021. Only, the values of this indicator for edible offals decreased continuously for ten of the considered twelve years.